Logika epistemiczna w rozumowaniu sędziego: [Epistemic logic in the judge's reasoning] (Studia Prawnicze / The Legal Studies, 1985)
Logic dealing with “known” and “unknown” interdependence is called epistemic logic by the author. As the knowledge is of a paramount importance in legal reasoning, epistemic logic, apart from logic of sentence, deontic logic is an indispensable element in legal reasoning. The model of a basic epistemic sentence is the following: “it is true, that it is (known, that p is true) false”.The author considers axiomatic problems of this type of logic, the problem of negation of cognizance and uncertainty and certain cases of application of epistemic logic in law.